Analysis of Milk Production and Quality of Friesian Holstein Cows Before and After Maintenance at the Maju Mapan Joint Business Group of Dairy Farmers in Malang - Yunan Alghifari; Amin, Muhammad Rijal Masyhur; Al Arif, M. Anam; Khotimah, Khusnul; Agus, Ali; Agussalim, Agussalim; Anam, Moh. Sofi'ul; Kurniawan, Muhammad ‘Ahdi (Universitas Airlangga, 2024)
ABSTRACT This study aims to analyze the variations in milk production and milk quality at the Maju Mapan Joint Business Group of Dairy Farmers in Malang before and after the outbreak of foot-and-mouth disease (FMD) in dairy cows. This study used fresh cow milk from dairy farmers who were members of the Maju Mapan Joint Business Group of Dairy Farmers in Malang. Purposive sampling was used to select the respondents. Out of a total of 300 dairy farmers at the Maju Mapan Joint Business Group of Dairy Farmers, 30 dairy farmers were selected as respondents. A sample of 10% the dairy farmers was taken to determine milk production and quality by recording data on milk production. The data were analyzed using the normality test and paired t-test. The results suggested significant differences in milk production and milk quality before and after the FMD outbreak at the Maju Mapan Joint Business Group of Dairy Farmers in Malang.